Coronary Flow Velocity Reserve in Burn Injury: A Prospective Clinical Cohort Study. Issue 5 (September 2016) - Caliskan, Mustafa; Turk, Emin; Karagulle, Erdal; Ciftci, Ozgur; Oguz, Hakan; Kostek, Osman; Moray, Gokhan; Haberal, Mehmet
Abstract : The authors sought to evaluate coronary microvascular function and left ventricular diastolic dysfunction using transthoracic Doppler echocardiography in burn patients. In this study, 32 adult burn patients with partial or full-thickness scald burns that were hospitalized and treated were included. The control group was matched for age and sex and was composed of otherwise healthy volunteers. Transthoracic Doppler echocardiography examinations and simultaneous laboratory tests for cardiac evaluation were performed on the sixth month after burn injury as well as with the control group. High-sensitivity C-reactive protein levels were significantly higher in the burn patients than in controls (5.17 ± 3.86 vs 2.42 ± 1.78; P = .001). Lateral isovolumic relaxation time was significantly higher in the burn injury group than in the control group (92.7 ± 15.7 vs 85.5 ± 8.3; P = .03). Baseline coronary diastolic peak flow velocity of the left anterior descending artery was similar in both groups. However, hyperemic diastolic peak flow velocity and coronary flow velocity reserve (2.26 ± 0.48 vs 2.94 ± 0.47; P < .001) were significantly lower in the burn injury group than in the control group. Coronary flow velocity reserve was significantly and inversely correlated with high-sensitivity C-reactive protein, burn ratio, creatinine, and mitral A -wave max velocity. At the sixth month of treatment, burn patients had high-sensitivity C-reactive protein levels during this period, suggesting that inflammation still exists. In addition, subclinical coronary microvascular and left ventricular diastolic dysfunction can occur in burn patients without traditional cardiovascular risk factors. However, these results must be supported by additional studies.